Impact of design patterns on software quality: a systematic literature review. Issue 1 (1st February 2020) - Wedyan, Fadi; Abufakher, Somia
Abstract : The impact of design patterns on quality attributes has been extensively evaluated in studies with different perspectives, objectives, metrics, and quality attributes, leading to contradictive and hard to compare results. The authors' objective is to explain these results by considering confounding factors, practices, metrics, or implementation issues that affect quality. Furthermore, there is a lack of research that connects design patterns evaluations to patterns development studies. Accordingly, they also aim at providing an initiate on how patterns structure and implementation can be improved, to promote software quality. To achieve their goals, conducted a systematic literature review by searching the literature for related studies. The study covers the period between years 2000 and 2018. They identified 804 candidate papers. After applying inclusion and exclusion criteria, they were left with 50 primary studies. Their results show that documentation of patterns, size of pattern classes, and the scattering degree of patterns have clear impact on quality. In case studies, researchers used different metrics applied to different modules. Controlled experiments have major design differences. Reaching consensuses on the effect of patterns requires considering influencing factors, using unified metrics, and an agreement on what modules to measure. Studying how to improve patterns modularity is recommended for future research.